Teaching strategies - Selvam, S.K. Planneer (New Delhi : A.P.H publishing, 2010)
This book illuminates and culls out the three areas of educational endeavour based as current research are necessary to ameliorate the education at different innovative methods and techniques. ABL, CAL, online, offline and virtual learning are broadly disseminated in the book. The need for early intervention programs for disadvantaged children and the efficacy of such programs are discussed in detail in the book. Concrete illustrations have been provided to show how education can be a tool for rural transformation. A critical appraisal of SSA also is provided. Ensuring academic freedom and quality in education are of paramount importance. These issues and the supportive measures needed for novice teachers have been studied in great detail. Thus the book provides a broad overview of the key issues in education, all based research and it proves to be immensely useful to all those interested in the field. This is a compiled edition. A school student as well as a researcher can find interesting material in this book. Most of the articles are contributions of eminent persons in the field of education. The very purpose of this edition is to make the students and the teachers know what is going on around them in the academic world. Even the entrepreneurs in the realm of education find it more beneficial. Some of the articles are modified or simplified versions.
Keywords: Effective teaching -- India; Educational innovations -- India; Educational innovations